The Neuroendocrine Cancer. Personal Comments and Operational Remarks - Andrea Cavallaro; Giorgio Maria Paolo Graziano; Marco Cavallaro; Antonino Graziano (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Indroduction: Neuroendocrine tumors (NEN) of the gastro-entero-pancreatic tract (GEP) are a group in themselves very heterogeneous of tumors that are different for the site of localization in the digestive tract (foregut, midgut and hindgut), both in relation to the pathological aspects, functional activity and nosographic classification. Materials and methods: In the period from January 2001 to July 2006 (III Clinical Surgery unit) and from January 2006 to October 2013 (Surgery of the Digestive Tract Unit), UOCS of the University Hospital of Catania has come to our observation 4 patients in the first period and six in the second period. Cases of NEN-GEP we observed allow to highlight how there are elements of clinical differences that make it difficult framing them. Results: Are summarized personal pathologic and therapeutic results. Discussion: The interest in the subject stems also from the fact that tumors NEN / GEP, whose detection is now more usual, are malignancies in which it appears increasingly important invasive activity. Despite the huge amount of data acquired, however, several features have yet to be investigated in order to better define the clinical behaviors, develop more precise diagnostic modalities and examine further possibilities for related treatment. Conclusions: The Authors suggest some recommendations for an appropriate, better treatment of these lesions.